Bayesian Estimation of Macroseismic Intensity from Post-Earthquake Rapid Damage Mapping. Issue 4 (November 2018) - Pittore, Massimiliano; Graziani, Laura; Maramai, Alessandra; Haas, Michael; Parolai, Stefano; Tertulliani, Andrea
The seismological community acknowledges the essential contribution of macroseismic assessment to the compilation of the seismic catalogs used for seismic hazard assessment. Furthermore, macroseismic observations are routinely employed by civil protection authorities in the aftermath of damaging events to improve their decision making. In this paper, we describe a novel methodology for the rapid, probabilistic estimation of macroseismic intensity in the epicentral area of a major event according to the European Macroseismic scale. The methodology includes mobile mapping and a collaborative online platform for rapid post earthquake reconnaissance. A Bayesian scheme is proposed to integrate direct damage observations and prior information, allowing consideration of ancillary data and expert judgment. According to a feasibility study carried out in the area affected by the 2016 Amatrice (Central Italy) earthquake, the proposed methodology should provide a reliable estimation of intensity, efficiently integrating further post earthquake building damage surveys.